2021
DOI: 10.1186/s12913-021-06854-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal education level and maternal healthcare utilization in the Democratic Republic of the Congo: an analysis of the multiple indicator cluster survey 2017/18

Abstract: Background Understanding how socioeconomic factors influence maternal health services utilization is crucial to reducing preventable maternal deaths in the DRC. Maternal education is considered an important associate of maternal health service utilization. This study aims to investigate the association between maternal education and the utilization of maternal health services, as well as present geographical and socio-economic disparities in the utilization. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
9
22
0
Order By: Relevance
“…This is consistent with previous evidence in other low- and middle-income settings. 26 , 27 , 28 , 29 Similarly, and also consistent with the available evidence, C-section rates were higher amongst mothers with access to private health insurance (including those who directly paid for the procedure). 30 , 31 , 32 , 33 We hypothesize that, mothers with higher socioeconomic status, better educated, private health insurance holders and those able to afford out-of-pocket health expenditures, may have the greater access to C-section services.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with previous evidence in other low- and middle-income settings. 26 , 27 , 28 , 29 Similarly, and also consistent with the available evidence, C-section rates were higher amongst mothers with access to private health insurance (including those who directly paid for the procedure). 30 , 31 , 32 , 33 We hypothesize that, mothers with higher socioeconomic status, better educated, private health insurance holders and those able to afford out-of-pocket health expenditures, may have the greater access to C-section services.…”
Section: Discussionsupporting
confidence: 78%
“…A previous study using the Peruvian Demographic and Family Health Surveys (ENDES, in Spanish) that C-section rates were 21.4% in 2009 and 34.5% in 2018%. 29 , 30 Although ENDES is a representative national survey, the use of secondary data from a survey might have resulted in reduced precision and accuracy of the estimated data at national and subnational levels. 29 , 30 Due to the implementation of some health policies and interventions at the regional level (first administrative division in Peru), a subnational characterization of C-section rates could provide detailed information to policymakers and local health authorities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-country study showed mothers with no education had 2.7 times higher risk of mortality than mothers with high education [55]. Educated women better utilize maternal health services [56, 57] and recognize pregnancy complications, prepare for births and obstetric emergencies [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older women are more likely to have attained higher education than younger women. Education increases women's access to and utilisation of healthcare information [ 31 33 ]. As a result, better-educated women tend to be more informed about their reproductive health than uneducated women.…”
Section: Discussionmentioning
confidence: 99%